Analysis and Detection of Weeds Using Artificial Neural Networks - Akandewa A; Linda NG (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2022)
Detection of weeds or weeds is one way to increase agricultural yields. Herbicides are one of the most effective drugs for dealing with weeds. The effectiveness of using herbicides is done by spraying correctly and on target. In this study we detect weeds using artificial neural networks with camera tools that capture vertically the object to be detected. The results of the study show that detection results using artificial neural networks produce fairly good accuracy.